Anthropometric characteristics of elite male taekwondo players based on weight categories - Mirali, M.; Faradjzadeh Mevaloo, S.; Bridge, C.; Hovanloo, F. (Journal of Science in Sport and Exercise, 2022)
Purpose: The aim of this study was to investigate the anthropometric characteristics of elite taekwondo players based on weight categories, and to determine if the length of the lower extremities might influence player`s success-level. A total of 59 elite male taekwondo players (22.02 ± 3.07 years) participated in this study. Methods: All anthropometric assessments were performed according to the standards and methodology of the International Society for Advancement of Kinanthropometry. The 18 anthropometrical variables were measured for each athlete and compared between 7 different weight categories. The players were also divided into two groups (national and international) and the ratios of sitting-height to stature were compared. Results: There were significant differences (P < 0.05) between weight divisions in stature, body mass index, percentage of body fat, endomorphy, and mesomorphy, which were greater (P < 0.05) in heavy weight groups than light weight groups, and ectomorphy, which was greater (P < 0.05) in very light weight groups compared with the other weights. There was no significant difference in lean mass index (P > 0.05) between weight groups. Sitting height/stature ratio was significantly different (P < 0.05) between the two groups, where the international group had longer lower extremities than the national group. Conclusion: The findings of this study provide a valuable framework to support talent identification programmes and the development of specialised preparatory strategies for different weight divisions with the sport.